“HIGGS DOMINO ISLAND” GAME ADDICTION AMONG TEENAGERS IN SURABAYA - Surya Jaya Purnama Putra; Suryanto Suryanto; Tatik Meiyuntariningsih (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
The aims of this study were: 1.) to identified forms of addiction, 2.) intensity of addiction, and 3.) factors of games which are sources of addiction. This research uses qualitative and the method used is the case study method. The subjects of this study were teenagers who played the game